Perancangan Arsitektur Teknologi Informasi di Dinas KOMINFO Kabupaten Semarang Menggunakan Enterprise Architecture Planning - Muhammad Luthfi Al Fath; Melkior NN Sitokdana (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Department of communication and Information Technology (KOMINFO) Semarang requires the design of appropriate information technology architecture in order to perform its function as a government institution that is able to provide excellent service to the community. Therefore, the application of Enterprise Architecture Planning (EAP) as an Information Technology Architecture Design methodology was chosen to make it easier to design the right information technology architecture.This study aims to design the architecture of Information Technology in the Department of communication and information Semarang using EAP methodology. The research methodology used in the form of literature studies and direct observation in the field to collect information about infrastructure, applications, and data available at the Semarang district communication and Information Office.The results of this study are several implementation plans that need to be done, such as hardware and software updates,human resources training,Local Government Application Development, Local Government Network Development, E Office and Website Development. Each domain has components that are interrelated and grouped into subdomains, making it easier to manage. The design of this information technology architecture can help the Semarang district communication and Information Office in improving the current information system and improving its performance in providing services to the community.